Interfaces in Condensed Systems
DOI: 10.1007/bfb0116257
|View full text |Cite
|
Sign up to set email alerts
|

Reversible light-induced phase transition in the system cetyltrimethylammonium bromide — water containing a crown-ether-bearing azobenzene

Abstract: Phase transition temperatures pT (nematic ~ isotropic) in the system cetyltrimethylammonium bromide --water (CTAB-H20) were measured in the presence of small amounts of trans AB15C5, an azobenzene derivative that bears two crown-ether moieties, pT decreased as a function of the AB15C5 concentration. This pT decrease can be ascribed to interactions of the crown-ether moieties with CTAB. The effect was reverted upon irradiation, i.e., upon photochemical formation of the water soluble cis form of AB15C5. Thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The most common isomerizable photosurfactants contain azobenzene or stilbene groups; the chromophore can be in the hydrophobic chain [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] or in the head group. 3,[18][19][20] As first suggested by Shinkai, 3 incorporation of an azobenzene group into the hydrophobic chains is expected to affect the hydrophilic-lipophilic balance through light-driven isomerizations.…”
Section: Cis-trans Isomerizationsmentioning
confidence: 99%
“…The most common isomerizable photosurfactants contain azobenzene or stilbene groups; the chromophore can be in the hydrophobic chain [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] or in the head group. 3,[18][19][20] As first suggested by Shinkai, 3 incorporation of an azobenzene group into the hydrophobic chains is expected to affect the hydrophilic-lipophilic balance through light-driven isomerizations.…”
Section: Cis-trans Isomerizationsmentioning
confidence: 99%
“…Alternatively, if surfactants contain a suitable chromophore, then UV−vis light can be used as an external trigger, eliminating the need for composition or temperature changes. Typical photosurfactants contain an isomerisable group, such as azobenzene or stilbene, in the hydrophobic chain or a photocleavable headgroup. The majority of studies have been with azo-containing surfactants, which undergo isomerization (e.g., refs −6) and/or photolysis. , With compounds of this type, dramatic changes in surface tension (Δγ), up to 40 mN m -1 , were reported. , Photoisomerization of a single chain cationic surfactant was shown to induce a maximum Δγ of around 13 mN m -1 (Du Nouy ring) . In the present paper, drop volume tensiometry (DVT) was used, which allows equilibrium γ values to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, upon illumination, these systems typically reach photostationary states comprised of a mixed population of trans and cis isomers, the composition of which is a function of the wavelength of light used to illuminate the system. Past studies have demonstrated that isomerization of azobenzene-containing molecules can be used to induce isothermal phase changes in thermotropic and lyotropic liquid crystalline systems. , Langmuir−Blodgett films of water insoluble amphiphiles containing azobenzene have also been used as “command layers” to direct the anchoring of liquid crystals and to control wetting behavior . In contrast to these past studies, our research focuses on control of interfacial properties by using water soluble surfactants that contain azobenzene.…”
Section: Introductionmentioning
confidence: 99%